DRUG DISTRIBUTION INFORMATION SYSTEM AT PT. ANUGERAH PHARMINDO LESTARI JAKARTA BASED ON JAVA NETBEANS - Ida Fitriani; Danang Sutrisno; Rudi Prasetya (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Drug Distribution Information System (DDIS) implemented at PT. Pharmindo Lestari Jakarta has changed the way companies manage and distribute pharmaceutical products. Developed using NetBeans' Java platform, the system has won numerous awards for its seamless integration and ease of use. DDIS provides real-time information on inventory levels, product expiration dates and sales data, enabling companies to make informed decisions about procurement and distribution activities. It also offers various features such as order tracking, billing and invoicing, which have greatly increased the efficiency of the company's operations. One of the main benefits of DDIS is its ability to integrate with other systems such as accounting software, which has eliminated the need for manual data entry and reduced the risk of errors. The system also provides comprehensive reporting capabilities, enabling companies to analyze sales trends, identify potential bottlenecks, and make informed decisions about resource allocation.